IMPACT OF WORKLOADS, PERSONALITY, AND WORK STRESS TOWARDS COUNSELING AND GUIDANCE TEACHERS AT PUBLIC SENIOR HIGH SCHOOLS IN RIAU PROVINCE - riswani, riswani riswani; Fitri, Rugaiyah; Kartikowati, Rr Sri (JERAM, 2017)
The purpose of this research is to obtain information about the impact of workloads, personality, and work stress towards counseling and guidance teachers at public senior high schools in Riau Province. The research was conducted at public senior high schools in Riau Province. The data were collected using a survey method involving 186 counseling guidance teachers as a sample of 348 populations. Data from each variable were collected by using a survey method and analyzed by using Path Analysis. The results show that: (1) There is a direct positive effect of workloads towards counseling and guidance teachers an public senior high schools in Riau Province; (2) There is direct positive impact of personality toward counseling and guidance teachers at public senior high schools in Riau Province; (3) There is a direct positive effect of work stress towards counseling and guidance teachers at public senior high schools in Riau Province; (4) There is a direct positive effect of work stress towards counseling and guidance teachers at public senior high schools in Riau Province; 5) There is a direct negative effect of personality on work stress towards towards counseling and guidance teachers at public senior high schools in Riau Province. The implication of this research is that overfullness can disrupt teachers’ performance. Therefore, there should be cooperation between school supervisors, principals and counseling and guidance teachers in overcoming fatigue. Keywords: Workloads, personality, work stress and overfullness